High Prevalence of Transfusion-Transmissible Infections among Volunteer Blood Donors in Rural Area of Eastern Democratic Republic of the Congo (D.R.C) - , Michel Kalongo Ilumbulumbu; , Joel Kambale Ketha; , Vianney Kambere Tshimanga; , Gabriel Kambale Bunduki; , Moise Muhindo Valimungighe; , Tecla Katungu Kitamwivirirwa; , Sylvie Visavingi; , Franck Katembo Sikakulya; , Alexandre Amini Mitamo (Archives of Current Research International, 2018)
Background: Transfusion safety investigations in sub-Saharan Africa are sparse, often limited to local initiatives. The provision of transfusion products must comply with the rules of good transfusion practice. This study aimed to evaluate transfusion practices in a rural area in the Eastern Democratic Republic of the Congo and identifying the main Infectious Transfusion Infections. Methodology: This was a retrospective study carried out from January to December 2017 and including 961 volunteer blood donors in the haematology department of the laboratory of the Referral Health Centre of Eringeti, in the Eastern Democratic Republic of the Congo. Results: Among the 961 volunteer blood donors, 139 (14.46%) donors were found with infections transmissible by transfusion. The sex ration of 1.6 in favour of males was observed and the group age below 20 years was the most affected. The majorities of donors were single, farmers, without any level of education and reside in the village of Eringeti. Syphilis, Hepatitis B virus, Human Immunodeficiency Virus, as well as Hepatitis C Virus, were more represented respectively with 38.1%, 30.2%, 20.1% and 11.5% followed by HIV-Syphilis, syphilis-hepatitis B and syphilis-hepatitis B and C co-infection in the same proportion (0.7%). Ancient donors were more affected by transmissible transfusion infections with 55.4%. Conclusion: Blood safety is an essential health goal. But it is by far to be accomplished in the rural areas of the Eastern Democratic Republic of the Congo. Thus, improving the selection of donors on one hand, and the progress made in the development of more sensitive screening tools and the introduction of innovative screening measures on the other side, enhanced with a modern bank of blood with qualified staff at the Eringeti Referral Health Centre may improve the quality and safety of the blood products administered to the needy population and could thus reduce the risks ITTs in this rural area.